ESEARCH OF THE PROPERTIES OF THE SELF-COMPACTED CONCRETE OVER TIME - Bugayevskiy, S.; Voronova, Ye.; Shtefan, O.; Zadorozhny, A.; Kovrevsky, A.; Bugayevskiy, M.; Бугаєвський, С. О.; Воронова, Е. М.; Штефан, О. М.; Задорожний, А. О.; Ковревський, А. П.; Бугаєвський, М. С.; et al. (Харьковский национальный автомобильно-дорожный университет, 2017)
Concrete mixture is examined as a complex multicomponent system that becomes a single unit and can be studied as a physical unity with certain rheological, physical and mechanical properties. Studying the change of properties of self-compacted concrete over time, as well as the effect of two-phasic introduction of super-plasticizer on properties of concrete mixture are presented in this article.
ДОСЛІДЖЕННЯ ВЛАСТИВОСТЕЙ БЕТОНУ, ЗДАТНОГО ДО САМОУЩІЛЬНЕННЯ, В ЧАСІ
ИССЛЕДОВАНИЕ СВОЙСТВ САМОУПЛОТНЯЮЩЕГОСЯ БЕТОНА ВО ВРЕМЕНИ
Keywords: viscosity; friction coefficient; self-compacting concrete mixture; obstacle crossing ability; time of flowing through a V-shaped funnel; columns; building; суперпластифікатор; бетон; здатний до самоущільнення; бетонна суміш; в’язкість; коефіцієнт тертя; суперпластификатор; самоуплотняющийся бетон; бетонная смесь; вязкость; коэффициент трения; 666.97